Nasal heterotopy in a Newborn Infant: A Case Report - Tuğba Barsan Kaya; Ayşe Aydan Köse; Ayşe Neslihan Tekin (Journal of Pediatric Research, 2018)
Glial heterotopias are rare, congenital, benign, midline, non-teratomatous extracranial glial tissues which are mostly present in the nose and may masquerade as encephalocele or dermoid cyst. These masses appear to share a similar embryogenic origin. Herein, we present a neonatal nasal glioma on the nasal root and glabella area. Although rare, because of their potential to connect to the central nervous system, these disorders are clinically important.